2022
DOI: 10.1093/rheumatology/keac132.025
|View full text |Cite
|
Sign up to set email alerts
|

OA25 Is it time for patient-initiated methotrexate monitoring?

Abstract: Background/Aims Regular blood monitoring is recommended to ensure safety in patients on methotrexate (MTX). During the COVID pandemic, British Society of Rheumatology (BSR) sanctioned a reduction in monitoring for patients stable on MTX for 12 months. In accordance Devon CCG approved changing local Shared Care Guidelines (SCG), reducing the frequency to six monthly in stable MTX patients. Our aim was to assess whether monitoring frequency changed during the pandemic, and if so whether any pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Recent research has suggested that the clinical impact of missing DMARD monitoring is minimal, with one study suggesting that reducing the frequency of methotrexate monitoring from 3 to 6 monthly did not increase abnormal test results nor cause harm to patients. 33 However, such analysis is easily confounded by patient-specific factors related to clinical risk, which influence the likelihood of monitoring occurring. For example, patients at lower risk of negative outcomes may be less motivated to attend monitoring, or less proactively followed up by clinicians.…”
Section: Future Researchmentioning
confidence: 99%
“…Recent research has suggested that the clinical impact of missing DMARD monitoring is minimal, with one study suggesting that reducing the frequency of methotrexate monitoring from 3 to 6 monthly did not increase abnormal test results nor cause harm to patients. 33 However, such analysis is easily confounded by patient-specific factors related to clinical risk, which influence the likelihood of monitoring occurring. For example, patients at lower risk of negative outcomes may be less motivated to attend monitoring, or less proactively followed up by clinicians.…”
Section: Future Researchmentioning
confidence: 99%